Engine oils and automotive lubrication - Bartz, Wilfried J (Mechanical engineering (Marcel Dekker, Inc.), 1993)
Discusses all the major aspects of automotive and engine lubrication - presenting state-of-the-art advances in the field from both research and industrial perspectives. This book should be of interest to mechanical, lubrication and automotive engineers, automotive and machinery designers as well as undergraduate and graduate students in these fields.